2013
DOI: 10.1007/s12160-013-9575-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Being Out About Sexual Orientation Uniformly Healthy? The Moderating Role of Socioeconomic Status in a Prospective Study of Gay and Bisexual Men

Abstract: The common assumption that disclosing one's sexual orientation is uniformly healthy may be less accurate (or inaccurate) for lower status groups. Future research should explore SES as context for minority stress and LGB health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 54 publications
0
74
0
Order By: Relevance
“…Higher education increases people's health literacy and cognitive skills, enabling them to make better informed health-related choices [4,27], including the importance of appropriate HIV testing and timely initiation of cART with better access to websites and community resources. Finally, education is linked with social and psychological factors, including sense of control, social standing and social support [26], and individuals with higher education may face fewer barriers to access HIV care and be more resilient to stigma [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher education increases people's health literacy and cognitive skills, enabling them to make better informed health-related choices [4,27], including the importance of appropriate HIV testing and timely initiation of cART with better access to websites and community resources. Finally, education is linked with social and psychological factors, including sense of control, social standing and social support [26], and individuals with higher education may face fewer barriers to access HIV care and be more resilient to stigma [28].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that universal HIV screening approaches such as those aiming at all pregnant women, as an alternative to targeted HIV testing policies based on HIV risk perception such as those aimed at MSM, could have the additional benefit to decrease socioeconomic inequities in accessing HIV testing. Whereas the former approach would offer a voluntary HIV test to all pregnant women, for MSM to be offered an HIV test, disclosure of unprotected sex with other men and/or gay identity becomes a prerequisite which is likely to be influenced by socioeconomic position [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…For some MSM, personal experiences of stigma, discrimination, and homophobia regarding their sexual orientation can result in adverse mental health outcomes, including depression, anxiety, elevated stress, and suicidal thoughts and attempts (16)(17)(18)(19)(20)(21). Discrimination by health care providers (22), limited access to gay-friendly health services (23), and barriers to health insurance (23)(24)(25) also can contribute to HIV-related disparities experienced by MSM.…”
Section: Adaptation and National Dissemination Of A Brief Evidence-bmentioning
confidence: 99%
“…In a longitudinal study of 564 gay and bisexual men, outness predicted physical health benefits for higher socioeconomic (SES) men but health problems for lower SES men. 25 The authors concluded that, for many reasons, being out may be more difficult for lower-SES people.…”
Section: Introductionmentioning
confidence: 99%